Monitoring system of implementation of the Promoting Mental Health at Schools (PROMEHS) program - Martinsone, Baiba; Stokenberga, Ieva; Grazzani, Ilaria (Frontiers in Psychology, 2022)
Effective school-based mental health programs are a research field with growing interest and great social value. At the stage of development and initial testing of the program, as well as during dissemination, and adaptation in other cultures, it is important that the implementation is carried out in the way that was originally intended. Fidelity or adherence is the most often used concept relating to the extent to which the implemented intervention corresponds to the originally intended program. Therefore, monitoring of the implementation is an essential element necessary to integrate into contemporary evidence-based program. The current paper describes the monitoring system developed for the Promoting Mental Health at Schools (PROMEHS) project. The monitoring was done on both the structural and procedural aspects of the program’s implementation, involving the evaluation of five core aspects: fidelity, dosage, quality, responsiveness, and adaptation. This methods article aims to describe the development of the monitoring system and to analyze the strengths of the qualitative-quantitative multi-informant approach in the monitoring of the intervention’s implementation. In the future, this would support further research on effectiveness of the PROMEHS program.